Writers and their readers: the phenomenon of collective readership in Dalmatia in the early 19th century (Libellarium: journal for research in the field of information and related sciences, 2011)
In the late 18th century and early 19th century, during a period of extensive changes in the writing and reading culture, there was an increase not only in the number of readers but also in the importance that was being attributed to them. This importance manifested itself primarily in an increasingly widespread collective patronage but also a rising number of inscriptions to the collective reader that flourished at about the same time as the collective patronage phenomenon. Although books continued to be dedicated to various dignitaries throughout this period, most frequently as a token of gratitude for financial support but also inspired by friendship and family, the writers, who still rarely lived off the fruits of their labour, started to adopt a different attitude towards the reader. Using examples drawn from analysis of the entire book production in Dalmatian printing and publishing centres Zadar, Split and Dubrovnik in the period between 1815-1850, this paper intends to show to what extent inscriptions to the collective reader, generally identifiable by the fact that they address an unspecified reader or an entire community of readers, can reflect a growing significance that started to be attributed to the reader as early as the end of the 18th century and particularly in the first half of the 19th century. The analysis focused on the number and context in which inscriptions of that type are found, their variants, meaning, as well as reasons for their introduction into practice. Research has shown that inscriptions to the general readership became a common and regular form of communication with an entire community of readers as far back as the ‘20s. Although they were still not the most common type of inscriptions and failed to reach the number of inscriptions to prelates, their continuity was maintained during the next two centuries, which was particularly noticeable in the ‘40s. Moreover, the general readership was mainly dedicated literary works - poetry collections printed on the occasion of emperor’s birthday, works of Dubrovnik literature, plays and biographies. A smaller number of books were of religious origin or those in the field of history, geography, social anthropology, linguistics and even architecture. Inscriptions were used in an effort not only to make books and reading popular but also to reinforce readers’ love for their national tongue, i.e., national consciousness in general, just the same as it was endeavoured to be done through subscription system. Moral-didactic and religious works were intended to strengthen readers’ spirit and morality. It has been concluded that continued increase in the number of inscriptions to the general readership as well as the fact that they flourished precisely during the period of significant changes in the field of reading culture witness of an increasing importance of readers that marked the first half of the 19th century.
Keywords: book inscriptions; writer; readers; collective reader; Dalmatia; 19th century